2020
DOI: 10.1039/c9cp06482f
|View full text |Cite
|
Sign up to set email alerts
|

Polaronic structure of excess electrons and holes for a series of bulk iron oxides

Abstract: With the use of a gap-optimized hybrid functional and large supercells, it is found that while the electron hole polaron generally localises onto a single iron site, the electron polaron localises across two iron sites of the same spin layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 78 publications
6
38
3
Order By: Relevance
“…In previous work we found that the excess electron in hematite is delocalized over two neighboring iron sites in the DFT electronic ground state. 26 According to electron transfer theory, this suggests that electronic coupling between 1-site localized excess electronic states is so large that they are are no longer stable states, that is, they no longer correspond to a minimum of the ground state potential energy surface. This is the case as soon as H ab > λ/2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous work we found that the excess electron in hematite is delocalized over two neighboring iron sites in the DFT electronic ground state. 26 According to electron transfer theory, this suggests that electronic coupling between 1-site localized excess electronic states is so large that they are are no longer stable states, that is, they no longer correspond to a minimum of the ground state potential energy surface. This is the case as soon as H ab > λ/2.…”
Section: Resultsmentioning
confidence: 99%
“…Though, one early estimate reported by Rosso and co-workers 17 for electron mobility is within a factor of 1.6 of our current best estimate. In previous work 26 we attributed the larger reorganization energy of cluster models to the absence of lattice strain effects present in the bulk structure, as well as the use of Hartree–Fock calculation which tends to overbind excess charge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations